Mild Cognitive Impairment: Its Past, Present, and Future - Kim, Ga Hye (Journal of Student Research, 2015)
As the baby boom generation nears retirement age and average life expectancy continues to rise, Alzheimer’s disease (AD) is quickly becoming one of the most relevant disorders of our time. There has been an increasing focus on early detection of AD for its various advantages from advanced planning to possible preventive treatment. As such, the main objective of this paper is to explore the transient stage between normal aging and dementia (centered on AD)—how its conceptualization has evolved throughout the past, present, and future. At the core lies the term “mild cognitive impairment” (MCI) as the paper traces its history, current standing, and topics of debate in the field. Its future implications as framed under the impending DSM-5 are discussed.